CUSTOMER RELATIONSHIP MANAGEMENT (CRM) STRATEGY PT. TELKOM THE RIAU Mainland TELECOMMUNICATION REGION IN MAINTAINING INDIHOME CUSTOMER LOYALTY - Zurani, Ikhma; Amalia, Wan Ecika (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2021)
Today's technological developments are increasingly diverse, one of which is the emergence of the internet which is one of the essential needs for some people. The competition between internet service providers is becoming more intense. For that a company needs to establish good relationships with customers to create long-term relationships. This study aims to determine the CRM strategy in the customer care unit at PT. Telkom Witel Ridar. The research concept used refers to the IDIC concept (identify, Differentiate, Interact, and Customize) by Peppers and Rogers. This study uses descriptive qualitative research methods with data collection techniques interview, observation, and documentation. The results of this study are in customer management with the concept of CRM IDIC is a form of CRM implementation of PT. Telkom Witel Ridar in managing relationships with customers that combines the communication skills of officers with technology. Starting from customer identification through NCX (New Customer Experience), My CX (Customer Experience), and starclick. Then differentiate customers based on existing customer data. Interact through various intermediary channels or directly. And also trying to modify various services and promos so that they can be tailored to the needs of customers.